(untitled) (Journal of Dhaka Medical College, 2016)
Background: Acute Kidney Failure (AKF) is the acute loss of kidney function over hours or days, the aetiology of which varies in different countries. Objectives: The study was aimed to find out the aetiology and see the immediate outcome of AKF in children in a tertiary level teaching hospital in Bangladesh. Methods: This prospective observational study was conducted from June 2011 to December 2012 in the Paediatric Nephrology Department of Dhaka Medical College Hospital, Dhaka. AKF was evidenced by presence of any two: serum creatinine raised >3 fold from the baseline, urine output <0.3ml/kg/hr for 24 hours or anuria for 12 hours. A total of 50 children with AKF were evaluated regarding their socio-demographic and clinical data. All underwent intermittent peritoneal dialysis and other necessary supportive care as needed. They were followed up for 3 months after enrolment. Results: Age of the children ranged from 5 days to 12 years. Among them, 33 were male and 17 female. Majority of the patient were from rural area and from a poor socioeconomic status. Out of 50 children majority (76%) were under 5 year age. The aetiology of AKF was mainly prerenal 66%, followed by renal 32 %, post renal 2%children. Among the pre-renal AKF 68% were due to diarrheal complications,12% neonatal AKF were due to severe perinatal asphyxia (PNA). Haemolytic uraemic syndrome, wasp envenomation and acute glomerulonephritis were the common renal causes of AKF. Post-renal cause of AKF was due to posterior urethral valve. The overall 38(76%) survived with normal renal functions, 10(20%) died and 2(4%) developed chronic kidney disease. The higher mortality rate was due to late referral, multi organ failure and severe degree of renal failure. Conclusion: This study suggests that diarrhoeal disease was the major cause of paediatric AKF. AKF is more common in infancy and associated with increased mortality. Common cause of neonatal AKF is severe perinatal asphyxia. J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 86-91